PERTUMBUHAN ANAK DARI IBU YANG MENDAPAT SUPLEMEN MULTI-MIKRONUTRIEN DAN ANAK DARI IBU YANG MENDAPAT SUPLEMEN BESI FOLAT SELAMA HAMIL (Studi follow up di Kabupaten Probolinggo, Jawa Timur) - Rahmadiani Wijayanti; Sri Sumarmi (Universitas Airlangga, 2016)
Recent studies have shown that maternal multiple micronutrient (MMN) supplementation improved birth weight but there is insufficient evidence that postnatal growth of children from mothers who received MMN are better than children from mother who received iron folic acid (IFA) during pregnancy. The aim of this study was to compare the growth of children aged 16–39 months from mother who received MMN and children from mother who received IFA during pregnancy. The design of this study was nested case control study from cohort study of reconceptional multiple micronutrient supplementation to Improve Maternal Iron Status and Pregnancy Outcomes (Laduni Program). The subject were 30 children randomly selected from the children of mothers who received MMN, and 30 other children randomly selected from children of mothers who received IFA. Variables observed in this study were birth weight from the health records, height-for-age z-scores (HAZ), weight-for-age z-scores (WAZ), and body mass index-for-age z-scores (BMIAZ) through direct measurements; nutrient intake from 2 x 24 hours dietary recalls. The average of children’s age in this study (±SD) was 28 ± 5,3 months. There is no difference in HAZ, WAZ, BMIAZ, and nutrient intake between the children of mothers who received MMN and children of mothers who received IFA. Most of the nutrient intake were inadequate as the diet were unbalanced and monotonous. Conclusion: maternal MMN supplementation during pregnancy has no effect on growth of 16–39 month old children if the nutrient intake is inadequate. Children should eat a variety of diet sufficienly for an optimal growth.Keywords:growth, maternal multiple-micronutrient, iron folic acid, children